ANALISIS SEMIOTIKA MAKNA LIRIK LAGU “MATAHARI TENGGELAM” KARYA HINDIA - Nur Kholis Abdul Rozaq; Buddy Riyanto (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
This study is motivated by the controversy surrounding the lyrics of “Matahari Tenggelam” by Hindia, which were perceived as ambiguous and even accused of containing heretical elements. This phenomenon sparked debates on social media between supporters and critics. The research aims to reveal the denotative, connotative, and mythical meanings within the song’s lyrics using Roland Barthes’ semiotic theory. Employing a descriptive qualitative method, data were collected through documentation of the lyrics and supporting sources. The analysis identified the signifiers and signifieds in each stanza, then interpreted them at three levels: denotation, connotation, and myth. The findings indicate that “Matahari Tenggelam” represents social criticism toward issues of injustice, lack of empathy, media influence, and moral degradation. The lyrics serve as an artistic expression reflecting emotional unrest and the disconnection between individuals and social reality, rather than an endorsement of deviant teachings. Keywords: Semiotics, Roland Barthes, Hindia, Matahari Tenggelam, Social criticism